Characterizing mortality in pediatric tracheostomy patients. (3rd November 2016) - Funamura, Jamie L.; Yuen, Sonia; Kawai, Kosuke; Gergin, Ozgul; Adil, Eelam; Rahbar, Reza; Watters, Karen
Abstract : Objectives/Hypothesis: To assess the longitudinal risk of death following tracheostomy in the pediatric age group. Study Design: Retrospective cohort study. Methods: Hospital records of 513 children (≤18 years) at a tertiary care children's hospital who underwent tracheostomy between 1984 and 2015 were reviewed. The primary outcome measure was time from tracheostomy to death. Secondary patient demographic and clinical characteristics were assessed, with likelihood of death using χ 2 tests and the Cox proportional hazards model. Results: Median age at time of tracheostomy was 0.8 years (interquartile range, 0.3–5.2 years).The highest mortality rate (27.8%) was observed in patients in the 13‐ to 18‐year‐old age category; their mortality rate was significantly higher when compared to the lowest mortality risk group patients (age 1–4 years, P = .031). Timing of death was evenly distributed: <90 days (37.6%), 90 days to 1 year (27.1%), and >1 year after tracheostomy (35.3%). Patients who underwent tracheostomy for cardiopulmonary disease had an increased risk of mortality compared with airway obstruction (adjusted hazard ratio: 3.53, 95% confidence interval: 1.72‐7.24, P < .001) and other indications. Adjusted hazard ratios for bronchopulmonary dysplasia (BPD) and congenital heart disease (CHD) were 2.63 and a 2.61, respectively ( P < .001). Conclusions: Pediatric patients with tracheostomy have a high mortality rate, with an increased risk of death associated with a cardiopulmonary indication for undergoing tracheostomy. The majority of deaths occur after the index hospitalization during which the tracheostomy was performed. BPD and CHD are independent predictors of mortality in pediatric tracheostomy patients. Level of Evidence: 4 Laryngoscope, 127:1701–1706, 2017